Human, Method and Material Analysis of Motivation for Providing Dpt-Hb-Hib Follow-up Immunization to Children Aged 18-24 Months in Karangtengah District, Sananwetan Regency, Blitar City: English - Syahril Ramadhan; Alfian Fawzi (Journal of Hospital Management and Services, 2019)
Immunization is a form of health intervention that is effective in reducing infant and under-five mortality rates. The purpose of this research is to identify man, method, material and analyze the effect of man, method and material on motivation to carry out advanced DPT-Hb-Hib immunization in children aged 18-24 months. The design of this study was an observational quantitative study with a cross sectional approach with a focus of research directed at analyzing the influence of man, method and material on the motivation to carry out advanced DPT-Hb-Hib immunization for children aged 18-24 months in Karangtengah Village, Sananwetan District, Blitar City with a population of a number of 35 respondents and a sample of 32 respondents who were taken using the simple random sampling technique. The results showed that Most of the respondents considered man, method and material in the sufficient category with 18 respondents (56.3%), method with 17 respondents (53.1%). Meanwhile, for the material with the number of respondents 18 (56.3%). For the motivation of respondents, 17 respondents (53.1%) were in the sufficient category. The results of the study used the test Multiple linear regression shows that with a p-value of 0.000 <0.05, H1 is accepted, so it can be concluded that simultaneously it exists the influence of man, method and material on the motivation to carry out advanced DPT-Hb-Hib immunization on children aged 18-24 months in Karangtengah Village, Sananwetan District, Blitar City with a magnitude of the effect of 83.8% . Respondents can participate in a series of activities that support toddler health. One of them is giving immunizations according to schedule so that in the community a Herd Immunity is formed. Immunization is still considered cost-effective, this is because if you calculate the costs incurred to provide vaccines are much cheaper than the cost of treatment, disability and the risk of death.